The world economy - Maddison, Angus (Development Centre studies., 2006)
This publication brings together two reference works by Angus Maddison: The World Economy: A Millennial Perspective, first published in 2001 and The World Economy: Historical Statistics, published in 2003. This new edition contains Statlinks, a service providing access to the underlying data in Excel format. These two volumes bring together estimates of world GDP for the past 2000 years and provide perspective on the rise and fall of economies historically.--Publisher description.